Polysaccharide-based hydrogels for cartilage regeneration - Chen, Ning; Li, Sidi; Miao, Congrui; Zhao, Qin; Dong, Jinlei; Li, Lianxin; Li, Ci (Frontiers in Cell and Developmental Biology, 2024)
Cartilage defect is one of the common tissue defect clinical diseases and may finally lead to osteoarthritis (OA) which threat patients' physical and psychological health.Polysaccharide is the main component of extracellular matrix (ECM) in cartilage tissue.In the past decades, polysaccharide-based hydrogels have shown great potential for cartilage regeneration considering unique qualities such as biocompatibility, enhanced cell proliferation, drug delivery, low toxicity, and many others. Structures such as chain length and chain branching make polysaccharides have different physical and chemical properties. In this review, cartilage diseases and current treatment options of polysaccharide-based hydrogels for cartilage defection repair were illustrated. We focus on how components and structures of recently developed materials affect the performance. The challenges and perspectives for polysaccharide-based hydrogels in cartilage repair and regeneration were also discussed in depth.